Factors Affecting Online Purchase Acceptance of Genuine Gemstone Jewelry - Lohploy, Jatuphat; Distanont, Anyanitha (Suan Dusit Graduate School Academic Journal, 2023)
This quantitative research aimed to study the factors affecting online purchase acceptance of genuine gemstone jewelry. The technology acceptance model, information system success model, and marketing mix theory were applied in this research, which was tested by content validity and reliability method of the questionnaire. Data analysis was performed by inferential statistics with exploratory factor analysis (EFA). The data were collected through online questionnaire from the sample of 440 consumers, who were genuine gemstone jewelry or high value jewelry online buyers. The result revealed that factors affecting online purchase acceptance of genuine gemstone jewelry consisted of eight factors: Marketing Mix and Seller, Information Quality, Service Quality, System Quality, Buyer, Perceived Ease of Use, Perceived Usefulness and Perceived Risk.